A Preliminary Study in Immune Response of BALB/c and C57BL/6 Mice with a Locally Allergic Rhinitis Model. Issue 4 (July 2023) - Zhang, Qidi; Zhu, Wanting; Zou, Zhixin; Yu, Wenting; Gao, Pei; Wang, Ying; Chen, Jianjun
Background: BALB/c and C57BL/6 mouse strains are commonly used in allergy research. The current study investigated the immunological differences between these two mouse strains with a locally allergic rhinitis model. Methods: Eighteen BALB/c and eighteen C57BL/6 mice received different doses of ovalbumin (OVA) intranasally for eight weeks (each mouse strain has three subgroups, 25 mg/mL group, 0.25 mg/mL group, and the PBS group). The allergic symptoms, OVA-specific serum antibody (IgE, IgG1, IgG2a), cytokines (IL-4, IFN-γ, IL-10) in the splenic culture supernatant, infiltrating eosinophils and goblet cells in local nasal mucosa were measured. RNA-seq technology was applied to detect differential gene expression in the local nasal mucosa. Results: With the same dose of OVA stimulation, the exacerbation of allergic symptoms was more pronounced in C57BL/6 than in BALB/c. BALB/c serum IgE, IgG1, and IgG2a gradually increased, and C57BL/6 produced fewer serum antibodies IgE and IgG1, while IgG2a never increased. BALB/c spleen cell culture supernatant IL-4 and IL-10 increased with increasing dose, and IFN-γ increased significantly in the intermediate dose group, while IL-4, IL-10, and IFN-γ did not increase in C57BL/6. The infiltration of eosinophils and goblet cells in both mice was proportional to the dose, while C57BL/6 was elevated more than BALB/c. RNA-seq suggested that the innate immune response, immune system process function, Jun kinase (JNK) pathway, and MAPKK pathway were upregulated in C57BL/6 compared to BALB/c. The core genes responsible for the differential immune response in both mice with allergic rhinitis were Kng2, Kng1, Gnb3, Lpar3, Lpar1, Pik3r1, Pf4, Apob, Rps9, and Fbxo2. Conclusion: There are significant differences in the immunologic responses between BALB/c mice and C57BL/6 mice. BALB/c mice developed mild local allergic inflammatory reactions and strong systemic immune responses. In contrast, C57BL/6 mice had stronger local allergic inflammatory responses and relatively mild systemic immune responses. Different mice strains can be selected according to the research purpose.